Analisis Kebijakan Penyelenggaraan Pendidikan Berbasis Uang Kuliah Tunggal Bagi Perguruan Tinggi Negeri Fakultas Ilmu Sosial Dan Ilmu Politik Universitas Diponegoro Semarang Jawa Tengah - Retnoningsih, Yenni Dyah; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Policy analysis is the cornerstone in the implementation of policies to determine education policy implementation process Tuition Single. Implementation of Single Tuition policy is a series of government policy measures include the establishment of educational policy which is not only understood and implemented, but also need to be analyzed, reviewed, assessed, evaluated and further developed. Operation Tuition Single enacted on the basis of circulars Director General of Higher numbers: 97 / E / KU / 2013 on the basis of Law No. 12 of 2012 which contains instructions to eliminate the entrance fee and to establish and implement UKT for students. The purpose enactment UKT is to simplify the process of payment of tuition fees and eliminate other extra costs that are difficult to be supervised by the state. With so expected that all the people of Indonesia will be easier access to higher education. To reveal the problem of research using qualitative methods are Descriptive Explorative. The purpose of the study is to examine the implementation of Single Tuition Policy in the Faculty of Social and Political Sciences, Diponegoro University. The collected data were then used to formulate recommendations as a step formulation of policy alternatives. Results of the study were found in the field showed that at the level of implemelntasinya still found some problems or weaknesses, both at the level of policy formulation and policy implementation. However, there are some advantages or the power of education policy implementation model Tuition Single. Furthermore, the reconstruction of an alternative model of education the implementation of Single Tuition will be reviewed from juridical aspects, reviewing the legal umbrella, budgeting, design of policy formulation and implementation, one of which includes implementing organizations. To be running well it is necessary to formulate regulatory or legal basis that can provide legitimacy in the implementation of policies, programs, and activities to support the implementation of education policies Tuition Single.